1986
DOI: 10.1002/ps.2780170503
|View full text |Cite
|
Sign up to set email alerts
|

Vapour pressure of permethrin

Abstract: The vapour pressures of the separate isomers of permethrin have been determined over a range of temperatures by two laboratories using different versions of the gas saturation method. A statistical analysis of the sets of data from the two laboratories shows no significant differences for the cis isomers but a small difference in the 20°C extrapolated values for the trans isomer exists. However, this difference is discounted as arising from experimental error and the mean values of the estimated vapour pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…2003) and in particular of malaria. In most studies, the insecticides used were synthetic pyrethroids (permethrin, deltamethrin, lambda‐cyhalothrin), which combine the properties of low to moderate mammalian toxicity (Wells et al. 1986; Curtis 1991; Zaim et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2003) and in particular of malaria. In most studies, the insecticides used were synthetic pyrethroids (permethrin, deltamethrin, lambda‐cyhalothrin), which combine the properties of low to moderate mammalian toxicity (Wells et al. 1986; Curtis 1991; Zaim et al.…”
Section: Resultsmentioning
confidence: 99%
“…Insecticide-treated bednets (ITN) were shown over the past two decades as one of the most effective methods of reducing man-vector contact in intra-and peridomiciliary transmission of vector-borne diseases (Curtis 1991;Curtis et al 2003) and in particular of malaria. In most studies, the insecticides used were synthetic pyrethroids (permethrin, deltamethrin, lambda-cyhalothrin), which combine the properties of low to moderate mammalian toxicity (Wells et al 1986;Curtis 1991;Zaim et al 2000), low volatility and high insecticidal activity.…”
Section: Insecticide-treated Netsmentioning
confidence: 99%
“…gambiae as has been shown in some experimental hut trials . The demonstration of a deterrent effect in earlier trials was somewhat unexpected given the low vapor pressure of permethrin (Wells et al 1986), which usually acts as a contact insecticide. Our study indicated that the deterrent effect may be due to early exit of mosquitoes rather than a decreased rate of entry.…”
Section: Discussionmentioning
confidence: 95%
“…The use of ITNs is an effective, relatively cheap and sustainable method of malaria control (Curtis et al ., 1990; Lengeler et al ., 1996; Chavasse et al ., 1999). The synthetic pyrethroids used for the treatment of the nets combine the properties of low to moderate mammalian toxicity (Wells et al ., 1986; Zaim et al ., 2000), low volatility and high insecticidal activity. ITNs have also been evaluated against phlebotomine sandflies and leishmaniasis in several countries, including Italy (Maroli & Lane, 1989), Burkina Faso (Majori et al ., 1989), Syria (Tayeh et al ., 1997; Desjeux, 2000), Sudan (Elnaiem et al ., 1999a, 1999b), Kenya (Mutinga et al ., 1992, 1993; Basimike & Mutinga, 1995), Colombia (Alexander et al ., 1995d) and Venezuela (Feliciangeli et al ., 1995; Kroeger et al ., 2002).…”
Section: Review Of Available Sandfly Control Methodsmentioning
confidence: 99%